Labour rights and the Catholic Church - Beckett, Paul, 1956- author.
1 online resource.
Keywords: "This book explores the extent of parallelism and cross-influence between Catholic Social Teaching and the work of the world's oldest human rights institution, the International Labour Organisation (ILO). Sometimes there is a mutual attraction between seeming opposites, who in fact share a common goal. This book is about just such an attraction between a secular organisation born of the political desire for peace and justice, and a metaphysical institution much older founded to bring peace and justice on earth. It examines the principles evident in the teachings of the Catholic Church and in the secular philosophy of the ILO; together with the theological basis of the relevant provisions of Catholic Social Teaching and of the socio-political origins and basis of the ILO. The spectrum of labour rights covered in the book extends from the right to press for rights, i.e., collective bargaining, to rights themselves - conditions in work - and on to post-employment rights in the form of social security and pensions. The extent of the parallelism and cross-influence is reviewed from the issue of the Papal Encyclical of Pope Leo XIII De Rerum Novarum (1891) and from the founding of the International Labour Organisation in 1919"--